The Role Of Financial Culture In The Demand For Islamic Finance In Algerian Banks - slimane, asma; hariri, abdelghani; bendaoudia, wahiba (Journal of Research in Finance and Accounting, 2023)
This study aims to highlight the role of financial culture in the demand for Islamic finance in Algerian banks, where the concepts related to both financial culture and Islamic finance were addressed, and to answer the problem of the study, we designed a questionnaire that includes a set of axes related to the study variables, and the study sample included 110 individuals. The study concluded with many results, the most important of which is that there is a statistically significant effect of each of financial knowledge and the desire to obtain financial education and Islamic financial knowledge on the demand for Islamic finance in Algerian banks. There is no statistically significant effect of financial awareness on the demand for Islamic finance in Algerian banks. Financial culture affects the demand for Islamic finance in Algerian banks by a small percentage that does not exceed 15.28%.